Prevalence of Soil-Transmitted Helminth Infections and Associated Risk Factors Among School Children in Dembecha Town, Ethiopia - Aleka Aemiro; Sissay Menkir; Abayeneh Girma (SAGE Publishing, 2024)
Soil-transmitted helminth (STH) infections are among the most common infections that affect the poorest and most deprived communities. In most developing countries, children aged 5 to 15 years are at risk for chronic helminth infection and associated morbidity. This study aimed to determine the prevalence of STH infections and associated risk factors among three government elementary schools in Dembecha town, Ethiopia. We conducted a school-based cross-sectional study involving 316 participants between November 2019 and March 2020. A systematic random sampling method was used to select study participants from the study schools. Data related to the sociodemographic characteristics of the study participants and risk factors for STH infections were collected using a pretested questionnaire survey. Parasitological examinations of stool samples were performed using the formal-ether concentration method. Study participants aged 5 to 15 years were enrolled in this study. The overall prevalence of STH infection was 21.5% (68/316). Ascaris lumbricoides ranked highest, with a prevalence of 11.4%, followed by hookworms 7.3%, Trichuris trichiura 1.9%, and Strongloides stercoralis 0.9%. Age groups of 10-15 years (AOR =3.109; 95% CI: 1.033, 9.350), residence in Kebele 2 (AOR =2.990; 95% CI: 1.082, 8.264), illiterate mothers (AOR =4.689; 95% CI: 1.410, 15.59), and a family size of 4-6 (AOR =3.286; 95% CI: 1.299, 8.313) were significantly associated with STH infections. The prevalence of STH infections remains an important health issue for study participants. Therefore, school deworming programs twice a year are crucially needed until the prevalence falls below the level of public health importance.